2022
DOI: 10.1093/ehjopen/oeac013
|View full text |Cite
|
Sign up to set email alerts
|

Multi-lead pacing for cardiac resynchronization therapy in heart failure: a meta-analysis of randomized controlled trials

Abstract: Aims Multi-lead pacing is a potential therapy to improve response to cardiac resynchronization therapy (CRT) by providing rapid activation of the myocardium from multiple sites. Here we perform a meta-analysis of randomized controlled trials to assess the efficacy of multi-lead pacing. Methods and Results A literature search was performed which identified 251 unique records. After screening, 6 studies were found to meet inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The influence of bias is less likely to be prominent in larger multicentre studies. As such, therapies which initially sound promising, such as AV/VV optimisation ( Brabham and Gold, 2013 ) and multipoint/multi-lead pacing ( Elliott et al, 2022a ) have lost momentum due to negative results in clinical trials of unselected patients. In actuality, their primary benefit could have been demonstrated by specifically targeting a non-responder population, where the potentially larger impact on measurable parameters may be adequate to power randomised trials at a reasonable sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of bias is less likely to be prominent in larger multicentre studies. As such, therapies which initially sound promising, such as AV/VV optimisation ( Brabham and Gold, 2013 ) and multipoint/multi-lead pacing ( Elliott et al, 2022a ) have lost momentum due to negative results in clinical trials of unselected patients. In actuality, their primary benefit could have been demonstrated by specifically targeting a non-responder population, where the potentially larger impact on measurable parameters may be adequate to power randomised trials at a reasonable sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The V3 trial ( Bordachar et al, 2018 ) and STRIVE-CRT ( Gould et al, 2022 ) are important negative trials which showed no significant difference in clinical or echocardiographic outcomes between standard of care and multi-lead pacing in unselected CRT populations. A meta-analysis of 415 patients by Elliott et al ( Elliott et al, 2022a ) again reported no difference between TriV pacing and conventional BiV pacing.…”
Section: Introductionmentioning
confidence: 97%